Being an Italian Medical Student During the COVID-19 Outbreak - Biavardi, Nicolo G. (International Journal of Medical Students, 2020)
Many students around the world have been wondering how their life will change since the very first outbreak of Covid-19. In my experience article I have tried to give a flavor of how has the academic world changed in quarantine. Difficulties and opportunities have been analyzed. Questions regarding the validity of e-learning have been posed. In an arduous period as the one we are experiencing, having an idea of what life could be in worst case scenario could be helpful.